Knowledge and attitude toward intimate partner violence among couples: a baseline findings from cluster randomized controlled trial in rural Ethiopia - Zeleke Dutamo Agde; Zeleke Dutamo Agde; Jeanette H. Magnus; Nega Assefa; Muluemebet Abera Wordofa (Frontiers Media S.A., 2024)
BackgroundIntimate partner violence (IPV) continues to be a major public health issue in Ethiopia. Studies have shown that knowledge and attitudes play a crucial role in predicting IPV. There is a lack of comprehensive evidence on the extent and factors associated with knowledge and attitudes toward IPV in many developing countries, particularly in rural Ethiopia. The objective of this study was to assess the level of knowledge and attitudes toward IPV and associated factors among couples in Central Ethiopia.MethodsA baseline survey involving 432 couples (432 pregnant women and 432 husbands) was conducted in July, 2023, in Hadiya Zone, Central Ethiopia. Data were collected using face-to-face interviewer-administered questionnaires. Multivariable logistic regression analysis was performed, and adjusted odds ratios with 95% confidence intervals were reported.ResultsThe findings revealed that 53.0% of women and 58.4% of men had good knowledge of IPV, while 56.0% of women and 65.6% of men held supportive attitudes toward IPV. Women's knowledge of IPV was significantly associated with age (25-34 years), educational attainment (secondary and higher/college education), antenatal care (ANC) visits, and husbands' alcohol consumption. Men's knowledge of IPV was associated with age at marriage <20, educational attainment (secondary and college/ higher education), monogamous marriage, and alcohol consumption. Predictors of women's attitudes toward IPV included marrying before the age of 20, partner smoking, and poor knowledge of IPV. Moreover, predictors of men's attitudes toward IPV included younger age (15-24), monogamous marriage, alcohol consumption, and poor knowledge of IPV.Conclusion and recommendationThe study found that more than half of couples had good knowledge of IPV, with a notable percentage also holding supportive attitudes toward it. Enhancing women's education, changing attitudes, ANC visits, and addressing male substance use would help in increasing couples' awareness of IPV and its consequences.